STRATEGI DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL DALAM PENERAPAN IDENTITAS KEPENDUDUKAN DIGITAL (IKD) DI KABUPATEN OGAN KOMERING ULU - Masagus A.Rahman Wempie; Eva Susanti; Santi Indriani (Program Studi Ilmu Pemerintahan Fakultas Ilmu Sosial dan Ilmu Politik Universitas Baturaja, 2024)
Digital Indonesian Identity Card (IKD) is a transition to digital form of e-KTP which makes it easy to access population information. The implementation of IKD is targeted at 50 million of the total number of mandatory KTPs throughout Indonesia's population. For the regencies, especially in OKU Regency, the target is 30% of the total number of mandatory KTPs in 2024. However, this target has not been achieved and the implementation of IKD by the OKU Regency Dukcapil Office is less effective. This research uses descriptive qualitative methods with data collection techniques consisting of interviews, documentation and observation. This research was carried out from March 4 - May 27 2024. The research uses strategy theory which has indicators of goal, environment, direction, action and learning. The results of this research show that the Population and Civil Registration Office of OKU Regency has not reached the target of 30% which has been set, and is still at 6.8% in May 2024, this is due to the lack of community support, and the lack of optimal socialization and activation of IKD to agencies which is aimed. The conclusion of this research is that the OKU Regency Population and Civil Registration Office has not achieved the targets that have been set. This cause is due to a lack of community support and there are not many benefits from IKD for public service needs for the community. The advice given is that the community should give full support to IKD. The government, especially regional heads, provides support in the form of issuing regulations for IKD obligations.